Study on Morphometric and Meristic Trait of Lady Fish Elops hawaiensis in the Northern Waters of Banten Province - Nico Sonyenzellnd (JURNAL PERIKANAN DAN KELAUTAN, 2015)
The ladyfish Elops hawaiensis is an important fisheries commodities in northern coast of Banten Province, which their availability were indispensible to the season. In this study the ladyfish were ranged between 17-36 cm. In morphometric measurement of the head part, haead length, width of open mouth, height of dorsal fin, height of the head, and operculum length have significant differences. The body scale of the ladyfish of Kronjo and Mauk has ranged 68-86, while ladyfish of Domas has ranged 60-82. Identification equation of the dorsal fin was D 20-24 and C 23-30 for caudal fin, the form of the caudal fin was a fork and has no hard radian. The anal fin has an equation A 14-15, ventral fin and pectoral fin has equation V 18-2 included in the meristic calculation.